Mycotoxins in Kenyan poultry feeds: Occurrence and use of bentonite and fumonisin esterase as a sustainable mitigation strategy to reduce effects of aflatoxins and fumonisins in broiler chicken and layer hens production - Ochieng, P.E. (Université de Liège, 2023)
This doctoral thesis consists of six chapters.